Al-Riba (Bunga) dalam Perspektif Sejarah & Agama - Abd Ghafur (Fakultas Ekonomi dan Bisnis Islam, 2018)
Riba is not a matter of concern in Islamic society, but actually outside of Islam also take seriously problem of usury. For, usury has become a discussion among Jews, Greeks, as well as Romans and Christians.Riba in the divine religion has been declared haraam, the Jews forbade the taking of flowers. This prohibition is contained in the Old Testament (the Old Testament) as well as the Talmudic laws. In Roman and Greek societies prohibited interest in its territory. Interest at that time was strictly prohibited by strict laws. The Christian side considers that the verse contained in Luke 6: 34-35 as a verse that condemns the practice of making flowers. In the Islamic religion also strictly prohibits the practice of usury. It is contained in the Qur'an and as-Sunna.